2012
DOI: 10.2147/cia.s36297
|View full text |Cite
|
Sign up to set email alerts
|

Detection of activities of daily living impairment in Alzheimer's disease and mild cognitive impairment using information and communication technology

Abstract: BackgroundOne of the key clinical features of Alzheimer’s disease (AD) is impairment in daily functioning. Patients with mild cognitive impairment (MCI) also commonly have mild problems performing complex tasks. Information and communication technology (ICT), particularly techniques involving imaging and video processing, is of interest in order to improve assessment. The overall aim of this study is to demonstrate that it is possible using a video monitoring system to obtain a quantifiable assessment of instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 27 publications
(24 reference statements)
2
59
0
1
Order By: Relevance
“…Further contributing to problems with the diagnostic criteria, characterizations of IADL problems are limited by scope and by the tools used to measure IADL impairment (Sacco et al, 2012). Recent studies have looked at IADLs using tools that measure the prevalence of deficits within IADL tasks or that use gross indexes to characterize IADL deficits, such as no problems to severe problems (Bombin et al, 2012;De Vriendt et al, 2013).…”
mentioning
confidence: 99%
“…Further contributing to problems with the diagnostic criteria, characterizations of IADL problems are limited by scope and by the tools used to measure IADL impairment (Sacco et al, 2012). Recent studies have looked at IADLs using tools that measure the prevalence of deficits within IADL tasks or that use gross indexes to characterize IADL deficits, such as no problems to severe problems (Bombin et al, 2012;De Vriendt et al, 2013).…”
mentioning
confidence: 99%
“…Schmitter-Edgecombe et al (2012) also found that MCI participants performed more poorly than healthy older adults on the Day-Out Task (DOT), a naturalistic test of functional ability that requires participants to complete multiple tasks and plan for an outing. Functional difficulties in MCI have also been revealed using Bsmart-home^technology in which participants were videotaped while performing daily activities in a room equipped with everyday objects (Sacco et al 2012). In one study, although individuals with MCI completed a performance-based test of IADLs with comparable accuracy to healthy older adults, their performance was significantly slower (Wadley et al 2008), suggesting reduced efficiency during everyday task completion.…”
Section: Evidence Of Functional Difficulties In Mild Cognitive Impairmentioning
confidence: 99%
“…Sacco et al [45] developed a Daily Activity Scenario (DAS) score, based on the Instrumental Activities of Daily Living questionnaire (IADL) that included watering plants, using a kettle, preparing a shopping list, using a telephone, watching TV and reading a newspaper. They demonstrated that such a scoring system could be used effectively in a smart home setting equipped with video monitoring to detect early functional impairment (although in their study there was relatively limited automatic recognition of IADL).…”
Section: Activity Monitoring and The Deficit Modelmentioning
confidence: 99%